Environmental Change and Its Pedagogical Implications: Enhancing Geography and Social Studies Education - Geoffrey Wall, Hifjir, Ika Listiqowati (Lembaga Bale Literasi, 2026)
Environmental change constitutes a complex global challenge that requires learners to integrate spatial, social, and systems-based perspectives within formal education. In response, this study examines secondary school students’ interdisciplinary understanding of environmental change within integrated geography and social studies instruction. The study focuses on how students construct interdisciplinary knowledge of environmental change and identify the key contributing factors that influence this process. A mixed-methods research design was employed, involving five secondary school students enrolled in integrated geography and social studies courses as primary participants and ten secondary school educators comprising five geography teachers and five social studies teachers as evaluators. Data was collected through a structured learning task addressing environmental change, an evaluation of a rubric encompassing overall interdisciplinary understanding and nine contributing factors, evaluator questionnaires, and semi-structured interviews. Quantitative data were analyzed using descriptive statistics, Pearson’s correlation coefficients, and path analysis, while qualitative data were analyzed through thematic analysis. The findings indicate that students demonstrated a moderate-to-high level of interdisciplinary understanding of environmental change. Socio-environmental reasoning, integrative explanation, and systems thinking emerged as the most influential factors directly shaping overall interdisciplinary understanding, whereas spatial awareness exerted an indirect influence through socio-environmental reasoning. In contrast, temporal awareness and critical reflection showed comparatively weaker effects. This study contributes to the field of environmental change education by providing empirical evidence on the interrelationships among interdisciplinary learning factors, offering methodological insights through the application of path analysis, and informing the design of integrated geography and social studies curricula that foster coherent and meaningful environmental learning outcomes.